SlpB Protein Enhances the Probiotic Potential of L. lactis NCDO 2118 in Colitis Mice Model - Belo, Giovanna A.; Cordeiro, Bárbara F.; Oliveira, Emiliano R.; Braga, Marina P.; da Silva, Sara H.; Costa, Bruno G.; Martins, Flaviano dos S.; Jan, Gwénaël; Le Loir, Yves; Gala-García, Alfonso; Ferreira, Enio; Azevedo, Vasco; et al. (Frontiers in Pharmacology, 2021)
Bacteria used in the production of fermented food products have been investigated for their potent role as modulators of inflammation in gastrointestinal tract disorders such as inflammatory bowel diseases (IBD) that cause irreversible changes in the structure and function of gut tissues. Ulcerative colitis (UC) is the most prevalent IBD in the Western countries population and it is marked by symptoms such as weight loss, rectal bleeding, diarrhea, shortening of the colon, and destruction of the epithelial layer. The strain Propionibacterium freudenreichii CIRM-BIA 129 recently revealed promising immunomodulatory properties that greatly rely on Surface-layer proteins (Slp), notably SlpB. We thus cloned the sequence encoding the SlpB protein into the pXIES-SEC expression and secretion vector and expressed the propionibacterial protein in the lactic acid bacterium Lactococcus lactis NCDO 2118. The probiotic potential of L. lactis NCDO 2118 harboring pXIES-SEC:slpB (L. lactis-SlpB) was evaluated in a UC-mice model induced by dextran sodium sulfate (DSS). During colitis induction, mice receiving L. lactis-SlpB exhibited reduced severity of colitis, with lower weight loss, lower disease activity index, limited shortening of the colon length, and reduced histopathological score, with significant differences, compared to the DSS group and the group treated with L. lactis NCDO 2118 wild type strain. Moreover, L. lactis-SlpB administration increased the expression of genes encoding tight junction proteins zo-1, cln-1, cln-5, ocln, and muc-2 in the colon, increased IL-10 and TGF-β, and decreased IL-17, TNF-α, and IL-12 cytokines in the colon. Therefore, this work demonstrates that SlpB recombinant protein, is able to increase the probiotic potential of the L. lactis strain to alleviate DSS-induced colitis in mice. This opening perspectives for the development of new approaches to enhance probiotic potential of strains by the addition of SlpB protein.